2001
DOI: 10.1590/s0101-81752001000200028
|View full text |Cite
|
Sign up to set email alerts
|

The gall midges (Diptera, Cecidomyiidae) from three restingas of Rio de Janeiro State, Brazil

Abstract: ABSTRACT. One hundred and eight species ofCecidomyiinae (Cecidomyiidae) were found in association with 53 species of plant distributed among 42 genera and 32 families at restingas of Barra de Marica, ltaipua~u and Carapebus. Ninety four gall midge species were cecidogenous, four predaceous, five inquilinous of galls and five were free living. Galling species were associated with 47 plant species belonging to 36 genera and 28 families. The majority of the galls occurred on the leaves (N = 63); 13 on buds; nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
0
32

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(154 citation statements)
references
References 12 publications
9
106
0
32
Order By: Relevance
“…The fact that 75% of the galls have been found in leaves, corroborate the pattern found in studies in Brazil, that indicates the leaf as organ most commonly attacked by gall makers (Maia et al 2008, Maia 2001, Urso-Guimarães et al 2003, Fernandes & Negreiros 2006 and with the world pattern found by Mani (1964). This pattern of occurrence in the leaves happens because the leaves are abundant resources and constant (Maia 2001), besides having a continuous flow of nutrients needed for the maintenance of photosynthesis (Whitham 1978). Another important factor is that females of Cecidomyiidae, most of the gall makers, has a very small size (1-5 mm), their ovipositor is fragile and can only lay eggs on tender tissues (Gagné 1994).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The fact that 75% of the galls have been found in leaves, corroborate the pattern found in studies in Brazil, that indicates the leaf as organ most commonly attacked by gall makers (Maia et al 2008, Maia 2001, Urso-Guimarães et al 2003, Fernandes & Negreiros 2006 and with the world pattern found by Mani (1964). This pattern of occurrence in the leaves happens because the leaves are abundant resources and constant (Maia 2001), besides having a continuous flow of nutrients needed for the maintenance of photosynthesis (Whitham 1978). Another important factor is that females of Cecidomyiidae, most of the gall makers, has a very small size (1-5 mm), their ovipositor is fragile and can only lay eggs on tender tissues (Gagné 1994).…”
Section: Discussionsupporting
confidence: 88%
“…This abnormal growth is due to increase in cell volume (hypertrophy) and/or cell number (hyperplasia). A rich insect fauna is associated with the galls and includes predators, parasitoids, tenants and successors, so galls represent a true micro habitat where several tri-trophic relations are established (Maia 2001). A recent study estimated the richness of insect galls in about 120,000 species (Espirito Santo & Fernandes 2007), making knowledge of this group essential for ecological studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the family Myrtaceae is frequently listed in surveys of galls in the Atlantic Forest of southeastern Brazil (Maia 2001;Maia et al 2008). it has been reported that, for the southern region of Brazil, which is dominated by Atlantic Forest and Pampas, galling insect species richness is greatest among host plants of the family Asteraceae (Mendonça 2007), whereas, in the cerrado, it is greatest among those of the family Fabaceae (Gonçalves-Alvim & Fernandes 2001;Maia & Fernandes 2004;Araújo et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Bruggmaniella byrsonimae (Diptera: Cecidomyiidae) Este cecidomiídeo induz uma galha no botão floral de B. sericea (Maia 2001a(Maia , 2001b e, comumente, são encontradas inflorescências com praticamente todos os botões galhados (Fig. 3U).…”
Section: Galhadoresunclassified